2018
DOI: 10.1111/imj.13939
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of cancer treatment providers regarding voluntary assisted dying in Victoria

Abstract: A survey of cancer treatment providers at our institution exploring their perspectives regarding voluntary assisted dying in Victoria and the imminent legislation showed that while almost all were aware of the Bill (92%), reported knowledge and understanding of it was much less (38%). As many clinicians supported the Bill as opposed it (28%); 44% were uncertain of their stance. Most were unwilling to directly provide voluntary assisted dying; if they did, would refer to palliative care services for ongoing sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…In this study, there was an almost even split between those reporting a positive attitude toward VAD and those reporting negative attitudes. This finding is consistent with recent Australian findings that health professionals working in the field of oncology failed to reach a clear consensus on VAD (Karapetis et al 2018;Yoong et al 2018), and international studies finding that health professionals hold diverse attitudes towards VAD (Young et al 1993). Together this indicates polarised views on the topic.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, there was an almost even split between those reporting a positive attitude toward VAD and those reporting negative attitudes. This finding is consistent with recent Australian findings that health professionals working in the field of oncology failed to reach a clear consensus on VAD (Karapetis et al 2018;Yoong et al 2018), and international studies finding that health professionals hold diverse attitudes towards VAD (Young et al 1993). Together this indicates polarised views on the topic.…”
Section: Discussionsupporting
confidence: 90%
“…In 2017, a survey conducted at a single Victorian institution showed that clinicians were divided on whether they supported VAD (28% support vs 28% opposed), with 44% being uncertain. 10 Similarly, a 2018 survey by the Medical Oncology Group of Australia similarly identified that 46% of members disagreed with VAD, 36% agreed and 17% were neutral on VAD. 11 The authors from both studies acknowledge their limited small sample sizes.…”
Section: Introductionmentioning
confidence: 99%
“…4 Consequently there is limited local data available to inform hospital approaches to implementation despite the shared goal of reducing suffering and providing good dying experiences for patients. 3,5,6 The experiences of clinicians in other jurisdictions have been mixed, with some experiencing considerable difficulties in working relationships, [7][8][9] whilst others found that relationships with colleagues could also be strengthened 7 . For some there was a lack of clarity in their role and scope of practice.…”
Section: Introductionmentioning
confidence: 99%